Pregnancy is influenced by more than just embryo ploidy: a retrospective study on preimplantation genetic testing - Sui-Bing Miao; Geng Tian; Zhen-Chuan Zhao; Xiao-Wei Wang; Jian Zhao; Cai-Ping Geng (European Journal of Medical Research)
Abstract Background Assisted reproductive technology (ART) has been widely used to treat infertility for more than four decades, but its efficacy is still lower than expected. Therefore, further exploration of the factors that affect the pregnancy outcome of ART treatment is necessary. Materials and methods A retrospective study of chromosome rearrangement carrier couples who requested preimplantation genetic testing (PGT) for structural rearrangements at the Fourth Hospital of Shijiazhuang was conducted between February 2019 and December 2022. Multivariate logistic regression analysis was performed to determine the risk factors for pregnancy. Results In total, 113 couples were transferred with a single euploid blastocyst, and 77 couples achieved pregnancy. Women with good-quality embryos transferred had a higher probability of pregnancy than women with poor-quality embryos transferred (OR 6.149, 95% CI 2.026–18.658). The chance of pregnancy was higher in women with a pregnancy history than in women without a pregnancy history (OR 3.181, 95% CI 1.157–8.747). The progesterone level on the day of trigger was positively associated with pregnancy (OR 2.605, 95% CI 1.226–5.538). Conclusion Embryo quality is significantly associated with the pregnancy rate in patients treated with PGT. Embryo ploidy is just one of the factors affecting embryo development. Future studies should focus on the molecular mechanisms of embryo development and develop corresponding detection methods.